Keratoconus management with partial topography-guided PRK combined with high-fluence CXL (Athens Protocol): results according to phenotype classification - Silva, Carlos Salgado (2019)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina